Наблюдения по экологии тяньшаньской одноцветной мышовки (Sicista tianschanika Sаlensky) - Смирнов, П.К. (Вестник зоологии, 1977)
Sicista tianschanika S a l e n s k y (1903) is widely distributed in the forest belt of the Jety-Oguzian ravine of the Terskej-Alatoo mountain ridge. Holes with nests in rotten stumps are the main type of shelter. Lability is detected in the choice of nest building material. Activity of animals is crepuscular, before the dew fall. At the last ten-day period of July two pregnant females are caught that in captivity gave birth to 5 and 6 young ones. The eatable feed is rather diverse.